Analysis of the Altman Z-Score Model in Predicting Financial Distress and Impact on the Value of the Firm - Zakiyatul Istifadia Istifadia; P. Pujiono (Golden Ratio of Auditing Research, 2026)
This study aims to examine the effect of financial distress on firm value in energy sector companies listed on the Indonesia Stock Exchange during 2022–2024. Financial distress is proxied by the Altman Z-Score, while firm value is measured using Tobin’s Q. A quantitative approach was employed using secondary data obtained from annual financial statements. The sample was selected through purposive sampling, resulting in 196 observations after data adjusment. Data were analyzed using IBM SPSS Statistics 27 through descriptive statistics, classical assumption tests normality, multicollinearity, heteroscedasticity, autocorrelation, and multiple linear regression with liquidity, operating cash flow, and debt to equity ratio as control variables. The results reveal that the Altman Z-Score has a positive and significant effect on firm value, indicating that firms with stronger financial health tend to receive higher market valuations. In addition, operating cash flow has a positive significant effect on firm value, liquidity has a negative significant effect, while the debt-to-equity ratio does not significantly affect firm value. This study provides empirical evidence that the Altman Z-Score serves not only as an early warning indicator of bankruptcy risk but also as a relevant determinant of firm value in an emerging market with relatively low market efficiency. The findings offer practical implications for investors and corporate managers in assessing financial health to support investment decisions and corporate financial policies.